Body mass index and skeletal muscle index are useful prognostic factors for overall survival after gastrectomy for gastric cancer: Retrospective cohort study. Issue 47 (20th November 2020) - Kim, Eun Young; Jun, Kyong Hwa; Kim, Shinn Young; Chin, Hyung Min
Abstract : Abstract: Among patients undergoing gastrectomy for gastric cancer, the impact of anthropometric indices on surgical outcomes is not well-established. The aim of this study was to evaluate the prognostic significance of the skeletal muscle index (SMI) and body mass index (BMI) on overall survival (OS) in patients with gastric cancer. A total of 305 patients who underwent curative gastrectomy for gastric adenocarcinoma between January 2005 and March 2008 were enrolled. Patients were classified into groups based on the SMI and BMI. The SMI was measured by preoperative abdominal computed tomography (CT). The SMI groups were classified based on gender-specific cut-off values obtained by means of optimum stratification. BMI groups were divided according to the World Health Organization definition of obesity for Asians. The mean SMI was 58.2 cm 2 /m 2 and the mean BMI was 23.2 kg/m 2 . One hundred fifteen (37.7%) patients had sarcopenia based on the diagnostic cut-off values (56.2 cm 2 /m 2 for men and 53.6 cm 2 /m 2 for women). Apart from gender, there were no significant differences in patient characteristics or surgical outcomes between the SMI groups. In the underweight group, tumor (T) stage, tumor-node-metastasis (TNM) stage, number of retrieved lymph nodes, D2 dissection, and hospital stay were significantly increased compared with the overweight/obese group. High and low BMI, and low SMI, were independent prognostic factors for OS (hazard ratio [HR] = 2.355, 1.736, and 1.607, respectively; P  = .009, .023, and .033, respectively). SMI and BMI did not impact perioperative morbidity in patients undergoing gastrectomy for gastric cancer. Both SMI and BMI are useful prognostic factors for OS in gastric cancer patients after gastrectomy.